Autoria Semiautomática de Efeitos Sensoriais em Vídeos 360◦ - Abreu, Raphael; Santos, Joel A. F. dos; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Creating multisensory experiences (mulsemedia) in 360° videos faces the challenge of synchronizing effects, a process that is laborious when manual and inflexible when fully automatic. This thesis proposes a semi-automatic approach that integrates deep learning (DL) recommendations while maintaining author control. The core proposal is a scalable cloud architecture with multiple recognition modules and an object tracking algorithm for spatial continuity, implemented in the SensorySynch360 web tool. A study with 81 users demonstrated that the approach significantly reduces authoring effort and time, while preserving usability and quality of experience.